Supplementing Chitosan Oligosaccharide Positively Affects Hybrid Grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) Fed Dietary Fish Meal Replacement With Cottonseed Protein Concentrate: Effects on Growth, Gut Microbiota, Antioxidant Function and Immune Response - Chen, Guofeng; Yin, Bin; Liu, Hongyu; Tan, Beiping; Dong, Xiaohui; Yang, Qihui; Chi, Shuyan; Zhang, Shuang (Frontiers in Marine Science, 2021)
Oligosaccharides have recently received much attention from researchers owing to their multiple biological activities. This study was conducted to investigate the effects of a diet with reduced fish meal and chitosan oligosaccharide (COS) supplementation on a hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂). Seven isonitrogenous and isolipidic types of diet were formulated to feed the groupers for 56 days. To prepare the feed, a reference diet (FM group) containing 55% fish meal was used. Concentrated cottonseed protein (CPC) was used to replace 45% of the fish meal protein, and different COS supplementation levels (0, 0.2%, 0.4, 0.6, 0.8, and 1%) were added. After an 8-week breeding trial, Vibrio harveyi bacteria were injected into the groupers for a 7-day challenge test. The results showed that the FM and COS0.4 groups showed the best growth performance among the groups (p < 0.05); however, there was no significant difference in the survival rate (p > 0.05). Unlike in the FM group, adhesion and breakage of the intestinal plica occurred in the COS0 group. The height and width of the gut fold reached maximum values in the COS0.4 group (p < 0.05). Microbiome sequencing suggested that there was a stable microbiota core in the gut of the groupers. With increasing COS levels, the abundance of both beneficial bacteria and conditional pathogens increased; the activities of serum glucose oxidase, catalase, and total superoxide dismutase also increased (p < 0.05). In the gut tissue, the activities of glutathione peroxidase, glutathione reductase, and glutamine increased first but then decreased (p < 0.05); the contents of lysozyme, acid phosphatase, complements C3 and C4, and IgM showed upward trends (p < 0.05). Compared with that in the FM group, the expression of IL-1β and TNF-α in the COS0 group was upregulated. Gene expression levels of TLR22, TGF-β, and Nrf2 increased first but then decreased with COS supplementation levels (p < 0.05). COS supplementation reduced the cumulative mortality of the groupers in the challenge test (p < 0.05). In general, the results of this study demonstrated that dietary COS supplementation enhanced growth performance, intestinal health, and antioxidant and immune responses of groupers fed with a low-fish meal diet. The optimal and acceptable levels of COS supplement were 0.45 and 0.4–0.6%, respectively; these values can provide a reference for developing aquatic prebiotics.